Viagens ecléticas, residências e obras: Maria Graham artista-autora-viajante - Maria de Fátima Lambert (Midas: Museus e Estudos Interdisciplinares)
The English author and artist Maria Graham (1785-1842) fulfilled a systematic thought about travel since her first stay in India, interspersing incursions into Europe and the emblematic residences in Brazil. Is there a museum [imaginary and singular] more eclectic than the one accomplished by the self-knowledge journey by a scholar or an artist? The case of the traveller Maria Graham, whose critical experiences echo in about 10 travel books, among them The Diary of a Journey to Brazil and a Stay in this Country during the years of 1821, 1822 and 1823, is exemplary – especially considering the period of socio-political consciousness in reference. Her literary work intertwines narrative with images, under the at most scientific requirements, and it can be related to the works of some other European authors who followed similar scientific and artistic missions, shaping an image of Brazil as seen by its visiting artists from the 16th century on. Accounts on places, mores and facts subsisted, underlining what was perceived as idiosyncrasies. Among the research on women-traveller-artists, that of Maria Graham highlights the characteristics of her on-the-spot investigation, adding the eclecticism of her viso-verbal testimonies, without losing herself in any form of dichotomous awareness. Mapping out the places she visited, pinning them down as articulating writing and drawing, she developed a work that appealed to her European readers. This female-traveller-researcher proceeded in such intersection of ideas, and provided her readers a peculiar perspective of her findings, of her one and only (and possibly “lonesome”) eclectic museum – weaved with the ability to surrender to the seduction of otherness, and the denunciation of societal conditions, while dealing with the complexity of her own emotions.